Effects of air pollution on health: A mapping review of systematic reviews and meta-analyses - Lorenzetti Branco J.H.* (2021)
© 2021 Elsevier Inc.Background: There has been a notable increase in knowledge production on air pollution and human health. Objective: To analyze the state of the art on the effects of air pollution on human health through a mapping review of existing systematic reviews and meta-analyses (SRs and MAs). Methods: The systematic mapping review was based on the recommendations for this type of scientific approach in environmental sciences. The search was performed using PubMed, Web of Science, Scopus, Cinahl, and Cochrane Library databases, from their inception through June 2020. Results: Among 3401 studies screened, 240 SRs and MAs satisfied the inclusion criteria. Five research questions were answered. There has been an overall progressive increase in publications since 2014. The majority of the SRs and MAs were carried out by researchers from institutions in China, the US, the UK, and Italy. Most studies performed a meta-analysis (161). In general, the reviews support the association of air pollution and health outcomes, and analyzed the effects of outdoor air pollution. The most commonly investigated health outcome type was the respiratory (mainly asthma and COPD), followed by cardiovascular outcomes (mainly stroke). Particulate matter (with a diameter of 2.5 μm (PM2.5) and 10 μm (PM10) or less) and nitrogen dioxide (NO2) were the most widely investigated pollutants in the reviews. The general population was the most common sample in the reviews, followed by children, and adults. The majority of the reviews investigated health outcomes of respiratory diseases in children, as well as cardiovascular diseases in all ages. Combining health outcomes and air pollutants, PM2.5 was included in a higher number of reviews in eight health outcomes, mainly cardiovascular diseases. Discussion: The majority of SRs and MAs showed that air pollution has harmful effects on health, with a focus on respiratory and cardiovascular outcomes. Future studies should extend the analysis to psychological and social aspects influenced by air pollution.